The Role Of Total Quality Management And Environmental Sustainability In Enhancing Corporate Green Performance In MSMES In Banten - Munawar Muchlish; Wulan Retnowati (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2025)
The aim of this study is to examine the role of Total Quality Management (TQM), and Environmental Sustainability (ES), in enhancing Corporate Green Performance (CGP) among MSMEs in Banten Province. This research utilizes primary data. The population of this study consists of all owners and managers of MSMEs in Banten Province, while the sample includes owners and managers of MSMEs based on local superior potential in Banten Province. The study employs a purposive sampling method and utilizes SEM-PLS v.26 and SPSS Version 27 as analytical tools. The findings of this study are as follows, TQM has a significant positive effect on ES, and CGP. ES has a significant positive effect on CGP.